2014
DOI: 10.1007/s00428-014-1713-4
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus status of penile squamous cell carcinoma is associated with differences in tumour-infiltrating T lymphocytes

Abstract: Meta-analyses show that approximately half of all squamous cell carcinomas (SCCs) of the penis are associated with a human papillomavirus (HPV) infection. As data about the tumour microenvironment of HPV-positive and HPV-negative penile carcinomas is scarce and conflicting, we examined tumour-infiltrating lymphocyte populations in such cases. The HPV status of 28 penile SCCs was determined by polymerase chain reaction, while the number and distribution of different lymphocyte populations were analysed by immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
(61 reference statements)
1
24
0
Order By: Relevance
“…The difference in patient outcomes between hrHPV + and non-virally induced penile cancer may be partially explained by different immune escape mechanisms ( 8 14 ). Surely, immunosuppressive and immunostimulating factors in the tumor microenvironment (TME) co-determine the course of disease in many different cancers, but relatively little is known about penile SCC ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in patient outcomes between hrHPV + and non-virally induced penile cancer may be partially explained by different immune escape mechanisms ( 8 14 ). Surely, immunosuppressive and immunostimulating factors in the tumor microenvironment (TME) co-determine the course of disease in many different cancers, but relatively little is known about penile SCC ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In penile cancer, various immune escape mechanisms in the TME have been studied (partly by our group) ( 8 14 ). In a multivariable analysis by Vassallo et al, presence of FoxP3-positive lymphocytes (presumably Tregs) was associated with poor disease free survival ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…HPV infection induces an immune reaction in an immunocompetent host, which leads to the generation of HPV‐specific memory T lymphocytes. Lohneis et al have suggested that the tumor microenvironment in HPV‐positive carcinomas is different from that in HPV‐negative carcinomas . Although additional studies are required to confirm this, one can hypothesize that the penile tumors with intense immune cell infiltrate are HPV‐positive and may respond to antiprogrammed cell death protein 1 (PD‐1) drugs.…”
Section: Molecular and Pathophysiological Pathways In Penile Cancermentioning
confidence: 99%
“…Lohneis et al have suggested that the tumor microenvironment in HPV-positive carcinomas is different from that in HPV-negative carcinomas. 51 Although additional studies are required to confirm this, one can hypothesize that the penile tumors with intense immune cell infiltrate are HPV-positive and may respond to antiprogrammed cell death protein 1 (PD-1) drugs. These drugs are currently being researched in other HPV-mediated cancers.…”
Section: Molecular and Pathophysiological Pathways In Penile Cancermentioning
confidence: 99%
“…Penile cancers are rare and they usually occur in uncircumcised men. [176] About half (40-50%) of the penile squamous cell carcinomas are related to the high risk HPV infection [52,[177][178][179][180] and mostly the basaloid and warty types of penile cancers are consistently related to HPV infection, whereas HPV DNA was only detected in some of the keratinizing and verrucous penile carcinomas. [179] Mainly HPV16 (69%) and HPV18 (13%) play a role in the development of penile squamous cell carcinomas.…”
Section: Penile Carcinoma and Anal Carcinomamentioning
confidence: 99%